A Personal Letter Found in Hermonassa - Pavlichenko, Natalia; Kashaev, Sergey (Hyperboreus, 2014)
A lead tablet, found in 2011 under the waters of the Taman Bay near the ancient townsite of Hermonassa, preserves the text of a private letter that can be dated to 450–440 BC. The text of the letter runs as follows: “Kledikos to Aristokrates. Aristokrates! It is Kledikos who writes to thee. I know that Mandrocharis, as diaitetes, is arbitrating for those evils that are taking place right here. Having arrived to the house of Sokrates [take ? … and] having gathered the remainder in one room, seal up [the door]!” Thus the letter allows us to assume, albeit cautiously, the existence of a court of diaitetai for private suits, in Hermonassa.